2020
DOI: 10.34172/ijer.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Trends of the Incidence of Cutaneous Leishmaniasis in the South of Fars Province, Iran, During 2007-2016

Abstract: Background and aims: Leishmaniasis is one of the most overlooked diseases in tropical areas, which can lead to many deaths and illnesses. The present study was designed to determine the trend of cutaneous leishmaniasis in the south of Fars Province (south of Iran) during 2007-2016. Methods: The population of this cross-sectional study consisted of all people with cutaneous leishmaniasis referring to the Center for Infectious Diseases in Larestan, Gerash, Evaz, and Khonj in the south of Fars Province during 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In this study, the highest number of PCL cases was observed in the age groups of 0-5 years old. This finding is in line with that of other studies in PCL endemic areas of Iran, including Golestan, Kerman, and Fars provinces [26,29,30]. Further, this study is supported by other studies in India, Turkey, and Pakistan that indicated PCL being more prevalent in younger age groups [6,7,27].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the highest number of PCL cases was observed in the age groups of 0-5 years old. This finding is in line with that of other studies in PCL endemic areas of Iran, including Golestan, Kerman, and Fars provinces [26,29,30]. Further, this study is supported by other studies in India, Turkey, and Pakistan that indicated PCL being more prevalent in younger age groups [6,7,27].…”
Section: Discussionsupporting
confidence: 92%
“…To determine the sample size using a similar study [ 22 ] and according to the formula of comparing the two means, taking into account the error level of 1%, power 90%, 72 people (36 people in each group) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…According to the latest population statistics registered in the apple system of the Ministry of Health, Treatment and Medical Education of Iran, the covered population in these three cities is approximately 272,000 people. In terms of climate, Larestan, Evaz, and Khonj are considered as arid regions, and the average annual rainfall in these regions from 2003 to 2010 was approximately 151.8 mm (Bazrafshan et al 2020a , b ). Larestan city is the largest city in the province of Fars in terms of area, which is located in the southern part of this province (Delam et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization has declared that COVID-19 is a recognized public health concern. This epidemic is the sixth public emergency of international concern after H1N1 (2002), polio (2014), Ebola in West Africa (2014), Zika (2016), and Ebola in the Democratic Republic of Congo (2019) (Bazrafshan et al 2020a , b ; Delam and Eidi 2020 ). COVID-19 causes severe respiratory tract infections in humans.…”
Section: Introductionmentioning
confidence: 99%